2004
DOI: 10.1124/jpet.103.063958
|View full text |Cite
|
Sign up to set email alerts
|

Different Regulation of Human δ-Opioid Receptors by SNC-80 [(+)-4-[(αR)-α-((2S,5R)-4-Allyl-2,5-dimethyl-1-piperazinyl)-3-methoxybenzyl]-N,N-diethylbenzamide] and Endogenous Enkephalins

Abstract: Among the different mechanisms underlying opioid tolerance, receptor desensitization would represent a major cellular adaptation process in which the role of receptor internalization is still a matter of debate. In the present study, we examined desensitization of the human ␦-opioid receptor (hDOR) produced by endogenous opioid peptides Leu-enkephalin (Tyr-Gly-Gly-PheLeu) and Met-enkephalin (Tyr-Gly-Gly-Phe-Met), and the contribution of internalization in this process. Results obtained with natural peptides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
5
30
1
Order By: Relevance
“…Alternatively, tolerance may be occurring since the behavioral effects of SNC80 to promote locomotor activity alone, as well as enhance amphetamine-mediated locomotor activity are subject to profound tolerance (Jutkiewicz et al, 2008). The lack of effectiveness of SNC80 after a 60 min perfusion in vitro would agree with the rapid development of desensitization and/or downregulation of the delta opioid receptor (Lecoq et al, 2004).…”
Section: Discussionmentioning
confidence: 57%
“…Alternatively, tolerance may be occurring since the behavioral effects of SNC80 to promote locomotor activity alone, as well as enhance amphetamine-mediated locomotor activity are subject to profound tolerance (Jutkiewicz et al, 2008). The lack of effectiveness of SNC80 after a 60 min perfusion in vitro would agree with the rapid development of desensitization and/or downregulation of the delta opioid receptor (Lecoq et al, 2004).…”
Section: Discussionmentioning
confidence: 57%
“…Because of the role that receptor internalization plays in opioid receptor desensitization and opioid tolerance, studies of biased agonism, with the end-point of receptor internalization, is a subject of contemporary interest. Opioid agonists, for example, differ in their ability to induce receptor internalization of μ (Koch et al, 2005), δ (Lecoq et al, 2004) and κ (Liu-Chen, 2004) opioid receptors. A striking example of this is the recently described μ agonist HERK which, unlike DAMGO and other internalizing μ opioid agonists, does not recruit β-arrestin and promote μ receptor internalization, even in cells that over express β-arrestin and the GPCR kinase, GRK2, (Groer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Photolabeling of Gα-subunits with azidoanilido-[α-32 P]GTP showed that constitutively active μ opioid receptors activate individual G proteins differently than those stimulated by DAMGO (Tyr-D-Ala-Gly-N-MePhe-Gly-ol) (Liu et al, 2001) and that peptide and non-peptide μ agonists induce different patterns of μ receptor phosphorylation (Chakrabarti et al, 1998). Moreover, opioid agonists differ in their ability to induce receptor internalization of μ (Koch et al, 2005), δ (Lecoq et al, 2004) and κ (Liu-Chen, 2004) opioid receptors. In this regard, recent studies showed that herkinorin (HERK) ((2S,4aR,6aR,7R,9S,10aS,10bR)-9-(benzoyloxy)-2-(3-furanyl) dodecahydro-6a,10b-dimethyl-4,10-dioxo-2H-naphtho-[2,1-c]pyran-7-carboxylic acid methyl ester) is a non-nitrogenous neoclerodane diterpene fully efficacious μ agonist (Harding et al, 2005), that, unlike DAMGO, does not promote β-arrestin recruitment and μ receptor internalization, even in cells that over express β-arrestin and the GPCR kinase, GRK2, (Groer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…After internalization, receptor could either recycle from endosomes to the plasma membrane and reduce desensitization, or degraded in lysosomes to decrease functional receptors on cell membrane and enhance desensitization [23] . In this study, prolonged CHA treatment did not induce DOR down-regulation, which suggests that receptor down-regulation is not a necessary consequence of phosphorylation.…”
Section: Wwwchinapharcom Cheng Y Et Almentioning
confidence: 99%
“…However, it is [9,13] , and heterologous desensitization was suggested to correlate with heterologous receptor phosphorylation [20] . DOR undergoes down-regulation after chronic selective agonist exposure, for different agonists the magnitude and time-course of receptor down-regulation varied [21][22][23] , nevertheless, all recent studies favor the idea that reduction of active opioid receptors from the cell surface would potentiate their desensitization.…”
Section: Introductionmentioning
confidence: 99%